In the eye of the beholder: A configurational exploration of perceived deceptive supplier behavior in negotiations - Katja Woelfl; Lutz Kaufmann; Craig R. Carter (Journal of Supply Chain Management, 2023)
Deceptive behavior in negotiations has been found to be widespread and to have harmful consequences. This study shifts the current research direction on deceptive negotiation behavior by adopting a target's perspective on deception and by using a configurational theorizing approach. Prior studies in supply chain management (SCM) and in other disciplines have studied deceptive negotiation behavior—as one specific form of opportunism—based on correlational approaches. In doing so, they have focused almost exclusively on the actor's (i.e., deceiver's) perspective—for example, investigating actors' motivations for using deception. As a result, a profound understanding of deceptive negotiation behavior from a target's perspective is lacking. In three studies, this research investigates what factors, on both the firm and individual levels, combine to lead purchasing managers (i.e., targets) to perceive supplier deception. The configurational analysis uncovers considerably more combinations of firm-level and individual-level factors that lead to perceptions of high supplier deception than combinations that lead to perceptions of low supplier deception. Thus, the contribution is twofold: First, the studies shift the perspective from the deception source to the deception target. Second, they uncover the causally complex nature of perceived deception in negotiations. Managerial implications include that purchasing managers, in their efforts to detect supplier deception, should move beyond paying attention to isolated factors, such as body language, and instead should focus on different combinations of power balances, negotiation stakes, and negotiator proficiencies.
Keywords: 330; configurational theorizing; deception; fuzzy-set qualitative comparative analysis (fsQCA); negotiation; opportunism